THE INFLUENCE OF GAMIFICATION STRATEGY TOWARDS ENGLISH VOCABULARY MASTERY AT THE NINTH GRADE STUDENTS OF MTS N 2 NORTH LAMPUNG ACADEMIC YEAR 2025/2026 - Ivonne Novenska Rahmadani; Rulik Setiani; Elis Susanti; Dewi Sartipa; Fina Oktavia; Reni Erawati; Intan Lestari; Dian Meirani (Universitas Muhammadiyah Kotabumi, 2023)
The problems in this research were that the ninth-grade students of MTsN 2 North Lampung had low English language skills, limitations in mastering English vocabulary, low learning motivation, and a less of interest in learning English. In addition, teachers had not applied much variation in English teaching techniques, and games were rarely used as a learning method in English classes. To overcome these problems, the researcher applied a gamification strategy as an alternative method to improve students’ English vocabulary mastery. This study aimed to find out the influence of the gamification strategy towards English vocabulary mastery at the ninth-grade students of MTsN 2 North Lampung in the academic year 2025/2026. The population of this research was all ninth-grade students, totaling 224 students. The sample consisted of two classes: IX.1 as the experimental class and IX.2 as the control class, each consisting of 33 students, selected using the purposive sampling technique. The research method used was a quantitative quasi-experimental design with a nonequivalent control group design. The data were collected through pre-tests and post-tests to measure students’ vocabulary mastery before and after the treatment. The instrument used was a multiple-choice test consisting of 40 validated and reliable items. The data were analyzed using normality, homogeneity, and hypothesis tests with a t-test formula. The results showed that the average post-test score of the experimental class was significantly higher than that of the control class. The t-test result indicated that tobserved > ttable (0.937 > 0.334) at a significance level of 0.05, meaning that Ha was accepted. This finding shows that there is a significant influence of gamification strategy towards English vocabulary mastery at the ninth-grade students of MTsN 2 North Lampung in the academic year 2025/2026. Therefore, gamification can be considered an effective and enjoyable learning strategy to enhance students’ engagement and vocabulary acquisition in English learning.